The Heparin-Binding Hemagglutinin of Nocardia cyriacigeorgica GUH-2 Stimulates Inflammatory Cytokine Secretion Through Activation of Nuclear Factor κB and Mitogen-Activated Protein Kinase Pathways via TLR4 - Ji, Xingzhao; Zhang, Xiujuan; Sun, Lina; Hou, Xuexin; Song, Han; Han, Lichao; Xu, Shuai; Li, Heqiao; Qiu, Xiaotong; Li, Minghui; Wang, Xuebing; Zheng, Ningwei; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Heparin-binding hemagglutinin (HBHA) from mycobacteria is involved in the dissemination of infection and the activation of the host immune response. However, the role of Nocardia cyriacigeorgica HBHA in its interaction with host cells remains unknown. In the present study, we describe the roles of N. cyriacigeorgica HBHA in interactions with epithelial cells and in organ colonization. Then, we investigated the mechanisms by which HBHA induced the production of inflammatory cytokines in macrophages. Immunofluorescent microscopy showed that HBHA adhered to A549 cells and HeLa cells and that the C-terminal fragment, which contains a Pro-Ala-Lys-rich domain, was responsible for adhesion. The deletion of the hbha gene in N. cyriacigeorgica mutant strains impaired adhesion to A549 cells and HeLa cells. In addition, the HBHA protein activated the mitogen-activated protein kinase (MAPK) and nuclear factor κB (NF-κB) signaling pathways and promoted the production of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-10 (IL-10) in macrophages. HBHA-mediated TNF-α production was dependent on the activation of c-Jun N-terminal kinase (JNK) signal pathways and IL-6 and IL-10 productions were dependent on the activation of extracellular regulated kinase(ERK) 1/2, mitogen-activated protein kinase p38 (p38), JNK, and nuclear factor kappa B (NF-κB) signaling pathways. Additionally, the HBHA-mediated activation of innate immunity was dependent on Toll-like receptor 4 (TLR4). Taken together, these results indicate that N. cyriacigeorgica HBHA not only adheres to epithelial cells and may be involved in organ colonization, but also plays a critical role in the modulation of innate immunity through MAPK and NF-κB signaling pathways via TLR4.